Mobile sensors based human activity recognition using machine learning with explainable ML - Rahman, Raihan; Osdi, Shafin Jami; Till, Sadia Sidran (Brac University, 2021)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science and Engineering, 2021.